Vers une mesure de la progressivité technologique - Simoneau, Marcel (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractIn this paper, the technological progress is measured by the relative change in total unit costs when input prices are constant and when the scale of production is optimal, that is where marginal cost intersects with average cost. The conceptual framework for a measurement of technological change is presented in the first section. Optimal scale and minimum average cost are therein illustrated, to elaborate, afterwards, on the decomposition of technical change in three major components. The approach to analyze the time pattern of substitution possibilities is given attention to as well as the analysis of heterotheticity and of various types of technological biases. The second section deals briefly with the econometrics of technology estimation on a sectoral basis. The technology is modelled through a "translog" cost function, that proves to be a second order approximation of any cost function. It is worthwhile to point out that this function may exhibit timevarying substitution elasticities as well as variable returns to scale. A brief discussion of the data used follows. The methodology was applied to Electrical and Chemical product industries, at the three digits level. In the third section, the empirical results are analyzed. They allowed to characterize the substitution profile, the scale and technological biases. They lead, also, to a decomposition analysis of technological change in three major components: efficiency effect, scale effect and bias effect. The analysis was related to 16 subsectors in the Canadian manufacturing, over the period 1961-1976.